2010
DOI: 10.1007/s00284-010-9634-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophytochrome-Dependent Regulation of Light-Harvesting Complexes in Rhodopseudomonas palustris Anaerobic Cultures

Abstract: Bacteriophytochromes (Bphs) are photoreceptors that help bacteria sense changes in light wavelength and intensity. Bphs contain a linear tetrapyrrole chromophore that, upon absorption of red or far-red light, undergoes a cis-trans isomerization that leads to a conformational change in the holoprotein. The conformation and type of Bph affects the expression of genes. The linear tetrapyrrole bound by Bphs is thought to come from O(2)-dependent cleavage of heme by a heme oxygenase. We have discovered that the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The LH4 complex predominates when this ratio is >1, and the LH2 complex predominates when the ratio is <1 (16,19). We found that deletion of either one of the RpBphP genes disrupted LH4 synthesis in response to low light intensity, similar to previous reports (7,8) (Fig. 1B and Table 1).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The LH4 complex predominates when this ratio is >1, and the LH2 complex predominates when the ratio is <1 (16,19). We found that deletion of either one of the RpBphP genes disrupted LH4 synthesis in response to low light intensity, similar to previous reports (7,8) (Fig. 1B and Table 1).…”
Section: Resultssupporting
confidence: 81%
“…Extensive in vitro work has shown that RpBphP2 and RpBphP3 can assemble with BV and function as light-regulated histidine kinases (7); however, because BV synthesis requires oxygen, it was thought that these RpBphPs might not always be associated with BV in vivo, particularly under anaerobic photosynthetic growth conditions (8,15,20,29). We found that RpBphP2 is bound to BV produced by HmuO in vivo in cells grown under extremely oxygenlimited conditions.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations